Association between cardiometabolic health and objectively-measured, free-living sleep parameters : a pilot study in a rural African setting - Cook, Ian.; Mohlabe, Matlawa; Makgopa, Herbert Mabalane (BMC Public Health, 2021)
Objectives: To investigate the relationship between objectively-measured, free-living sleep quantity and quality, and cardiometabolic health, in a rural African setting in 139 adults (≥40 years, female: n = 99, male: n = 40). Wristmounted, tri-axial accelerometry data was collected over 9 days. Measures of sleep quantity and quality, and physical activity were extracted from valid minute-by-minute data. Self-reported data included behavioural, health and socio-demographic variables. Biological data included body composition, resting blood pressure and fasting blood glucose, insulin and lipids. Logistic regression models were constructed with insulin resistance (IR) and cardiometabolic (CM) risk, as dependent variables, adjusting for socio-demographic, behavioural and biological factors. Results: Nocturnal sleep time was longer in females (p = 0.054) and sleep quality was better in males (p ≤ 0.017). Few participants slept > 9 h/night (4–5%), and 46–50% slept < 7 h/night. IR and CM risk was higher in females (p ≤ 0.006). In adjusted models, sleep variables were independently associated with IR (p < 0.05). Sleep quantity was nonlinearly associated with CM risk (p ≤ 0.0398), and linearly associated with IR (p ≤ 0.0444). Sleep quality was linearly related with CM risk and IR (p ≤ 0.0201). In several models, sleep quantity and sleep quality measures were concurrently and significantly associated with IR (p ≤ 0.044).
Journal article published in the journal of Sleep Science and Practice
Keywords: Insulin resistance; Metabolic syndrome; Anthropometry; Accelerometer; Actigraphy; Movement monitor; Measurement; Metabolic syndrome; Insulin resistance; Actigraphy; Sleep